The Analysis of Factor that Associated the Antenatal Care (ANC) Visit in Pregnant Woman during the COVID-19 Pandemic at Blooto Health Center, Mojokerto - Bella Ayu Nurfitriyani; Novia Indah Puspitasari (Media Gizi Kesmas, 2022)
Background: The COVID-19 pandemic situation has harmed various sectors. Maternal and child health services are also affected in terms of access and quality. Based on the health profile of Mojokerto City in 2021, Blooto Health Center has the highest K1 (100.7%) and K4 (98.1%) coverage in 2020 compared to other health centers in Mojokerto City. In 2021 in the first quarter of K1 coverage decreased compared to 2020. In January 2020 and 2021, it was 10% and 8.63%, February 2020 and 2021 were 19% and 17.79%, and March 2020 and 2021 were 29, 4%, and 28.3%.   Objectives: This study aims to analyze what factors are associated with Antenatal Care (ANC) visits to pregnant women during the COVID-19 pandemic in the work area of the Blooto Health Center, Mojokerto City. Methods: This study used a cross-sectional research design. The research population was 182 pregnant women with a sample of 79 pregnant women. The sampling technique is simple random sampling. The independent variables of the study were education level, employment status, disease history, age, parity, knowledge, attitude, application of health protocols, distance from residence to health facilities, the role of medical personnel, and availability of health protocol facilities at health care facilities. The dependent variable of the study was antenatal visits. Primary data collection using online questionnaires and secondary data, namely the maternal cohort book. Data analysis used univariable and bivariable analysis by calculating the Prevalence Ratio (PR) value. Results: There is a relationship between education level, knowledge, attitude, application of health protocols, the distance of residence, role of medical personnel, and availability of health protocol facilities with ANC visits during the COVID-19 pandemic. Meanwhile, age, employment status, disease history, and parity were not related to ANC visits during the COVID-19 pandemic. Conclusions: Education level, knowledge, attitude, application of health protocols, the distance of residence, role of medical personnel, and availability of health protocol facilities related to ANC visits during the COVID-19 pandemic. Health workers and community leaders are expected to provide education to pregnant women on the importance of doing ANC checks and apply health protocols during the pandemic.